IT-INDUSTRY’S OFFICE INTERIOR DESIGN EVOLUTION - Полякова, О. В.; Кисіль, С. С.; Булгакова, Т. В.; Півницька, Ю. В. (Art and Design, 2020)
Identification of trends in the planning organization and interior design of office spaces of the IT-industry, as well as an analysis of their changes over the course of the industry’s development. A study of the office spaces design evolution based on historical-artificial, architectural-planning, functional analysis. The source of the research became scientific and journalistic articles, domestic and foreign design developments of office spaces. We conducted an analysis of studies on the organization of the working environment in the IT-industry companies. It has been established that the “information technologies” include not only modern computer tools for processing and exchanging information, but also more traditional ones – telephone, mail, press, etc. — which became the prerequisite for a broad historical review. As a result of the analysis of historical periods of the office interior design development, the main stages of their formation are determined: the end of the 19th century – traditional office; 1900-30s – open-plan tayloristic office; 1950s – office landscape, 1960s – structural office; 1960-80s – cubes; 2000s – casual office. The advantages and disadvantages of the main historical types of planning solutions for the organization of office space are identified. The concept of the design of modern "mobile offices" in the environment of open-plan office spaces is disclosed. A retrospective review of the working environment of IT-industry specialists has been made. The main trends of the historical stages of the interior design of the IT-industry offices from the end of the 19th century to the present are analyzed and generalized. Practical significance of the study is determined by the expansion and deepening of knowledge about the evolution of IT-industry office interior design and can be used in the practice of designing appropriate environments.